Penerapan Prinsip Piercing the Corporate Veil terhadap Pelanggaran Fiduciary Duty - Yessira Dianita (Lembaga Pengembangan Kinerja Dosen, 2025)
This study examines the application of the Piercing the Corporate Veil doctrine in cases of fiduciary duty violations by the President Director of PT Bakara Bumi Energi, based on the Jakarta Central District Court Decision No. 451/Pdt.P/2019/PN.JKT.Pst. Using a normative juridical approach, the research analyzes primary and secondary legal sources, including Law No. 40 of 2007 on Limited Liability Companies and relevant court rulings. The findings reveal that the President Director's failure to provide transparent financial reports and operational information constitutes a breach of fiduciary duty, encompassing duties of loyalty and care, leading to financial losses such as tax arrears and reputational damage. Furthermore, this breach justifies the application of the Piercing the Corporate Veil doctrine to hold the director personally liable, as supported by similar judicial precedents. The study concludes that enforcing this doctrine enhances corporate governance and accountability, recommending clearer regulatory frameworks for broader application to directors and other corporate organs.